REDEFINISI KECANTIKAN DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEREMPUAN BALI, DI KOTA DENPASAR - Wiasti, Ni Made (PIRAMIDA; Vol. 6, No.2 Desember 2010, 2012)
Beauty is not an independent entity. It deeply roots in the culture of a particularcommunity. Such a culture is influenced by environmental conditions where thecommunity lives. On that account, beauty poses a social construction created by humanbeings. It changes all the times in accordance with the tastes and interests of thecommunity because it is indeed constructed by the community itself. In the Balinesecommunity, it is constructed that woman is considered beautiful if she has physicalbeauty and charming personality (inner beauty).Furthermore, since the modernity engulfs the world, the concept of beauty is morereferring to the construction of market and capitalistic ideology. The presence ofadvertisement and market does not only offer body care and beauty products, but at thesame time they also offer the concept of ideal woman image. Today, a woman consideredbeautiful if she has white skin, slim body and symmetrical face. Having passed through aseries of battles between capitalism and local values, the concept of beauty puts moreemphasis on physical beauty than any other consideration. Mass media, advertisement,fitness centers and beauty salons become important agents of change. The presence ofcapitalism has resulted in revitalization of Balinese culture, including the beauty ofwomen coming into view not only in the religious and customary moment but also inday-to-day life. Even, beauty is used as a means to achieve an objective in the occupationor career.
Keywords: redefinition of beauty, women productivity